PERFORMANCE IS A PHENOMENON OF CONTEMPORARY ART - GARAFONOVA, Olga; YASHCHENKO, Inna; DEREVIANKO, Diana; YANKOVYI, Roman (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The growing popularity of performance art makes it a striking phenomenon of international socio-cultural reality. Bright, protest form of artistic expression of the 1960s - 1970s in the late twentieth - early twentieth century. acquires the status of one of the most popular genres of contemporary art. Today, performances take place in many major museums around the world, elements of the genre are borrowed from modern mass and protest culture, and the transliterated term itself acquires new meanings and is used in different contexts. Existing and developing within the "field of art" (international institutions, the professional community, criticism, etc.), performance affects all aspects of human life without exception, and is a modern phenomenon of human life. The performance has a huge communicative potential, as it is designed to actively influence the audience or interact with the audience. It illustrates one of the trends in contemporary art: shifting the emphasis from the artist to the viewer. The high degree of significance of the recipient in the process of perception of art and increasing the role of context inevitably change the boundaries of art, having a significant impact on the relationship between art and society. This article is devoted to the consideration of philosophical views on performance, the basic principles of modern art, the characteristics of performance in everyday life, as well as analyzes the philosophical and ideological ideas underlying minimalism as a way of life.